ENVIRONMENTAL VIEWS OF STUDENTS ATTENDING SCHOOL OF MEDICINE, MALTEPE UNIVERSITY AND CONFOUNDING FACTORS - (:unkn) unknown (INT SCIENTIFIC CONFERENCE SGEM, 2011)
Introduction and Purpose: Environment is multi-dimensional notion that it has cultural, political, economic, ecologic, social and psychological dimensions in addition to nature-related dimension. Impacts of environmental problems and negative consequences of those impacts on the society increases importance of subject's knowledge, awareness, attitudes and behaviors. Knowledge on environmental views of doctor candidates and arranging education programs accordingly will make contribution to the solution of the problem. Material and Method: This study is a cross-sectional trial which was conducted on Grade 1-6 students attending School of Medicine, Maltepe University between I October and 30 November 2010. All students (n = 167) were enrolled into the study and 147 students (88.02 %) could be reached due to various reasons. In this study conducted for determining knowledge, attitude and behavior of students on environmental awareness, 44-item questionnaire form was applied. Results: It was observed that mean Environmental View Sub-scale scores of female students were higher than that of male students (p=0,005). It was found that students living with house mates had higher mean Environmental View Sub-scale scores than ones living with the family or alone (p=0.017). It was found that mean Environmental View Sub-scale scores obtained students living alone were significantly lower than that of students living with family, house mates and siblings - relatives (p=0.025). Absolute agreement was stated by 4.8 % of participants to the question They make exaggerations about endangered livings; there is always many living organisms in the nature. It is not important that some of them are endangered, by 5.4 % to the question Construction of luxurious highways instead of assigning monetary resources to historical places will be more beneficial to our country, by 6.1 % to the question Erosion is no more experienced in our country, by 2.7 % to the question insecticides used in the agriculture are environment-friendly and by 6.1 % to the question There is no problem in selling lands no more characterized as forest in order to provide income to the state. The choice of I absolutely disagree was marked by 44.22 % to the question The state should allow construction of tourism oriented buildings in national parks and forests, by 53.7 % to the question wetlands areas should be better dried for construction of residences, by 48.3 to the question Waste produced by human is of no problem since the nature detoxifies itself and 49.0 % to the question Ozone layer is particularly narrowed above land of U.S there is no danger towards Turkey. The choice of I partially agree was preferred by 19.0 % to the question turning off the lights when I leave the room will not provide a considerable energy saving, by 15.6 % to the question The water capacity of the world is far beyond the risk of pollution caused by human, by 17. % to the question Rapid consumption of natural resources is an important problem, 14.3 % to the question One important problem of Turkey is unplanned urbanization and 16.3 % to the question Gradual global warming may cause disasters in the future. Conclusion and Advices: The fraction of society such as doctors and teachers, who should be very aware, is anticipated to have more knowledge on and be largely interested in this issue. In this context, this issue should be involved in all formal and non-formal education programs, particularly in school of medicine, and methods increasing awareness and causing positive changes in attitudes and behaviors should be used in the education.
Keywords: Environment; Environmental View sub-scale; Students of School of Medicine